Archaeology goes to high school : Practical approach to archaeology teaching in high school - Vijand, Liia (JSSE - Journal of Social Science Education, 2019)
Purpose: The study investigated how various school subjects can be integrated into archaeology teaching and how this could lead students towards empathy and a more sustainable worldview. Design/methodology/approach: To meet the purpose of this multiple-case study, optional archaeology course development (2011-2019) and students’ questionnaires and feedback group A (2018) and group B (2019) and various empirical material, was analysed in cross-case methods. Findings: Archaeology interdisciplinarity and analysing long-term human behaviour supports an understanding of human nature, emphasizes empathy and tolerance, and encourages social cohesion. Research limitations/implications: The study was carried out in Estonia as a multiple-case study and further research, especially in the empathy part, is needed for further conclusions. Practical implications: Archaeology is interdisciplinary and therefore as a school subject it links together various and sometimes abstract subjects. It gives an understanding of long-term human behaviour, which allows developing students’ empathy and tolerance.